Modal Kapital Pimpinan CV. Penerbit Lakeisha terhadap Terbitan Genre Buku Fiksi Tahun 2023 (Arena Produksi Kultural) - Sholekah, Saskia Hasri; Mukafi, Muhammad Hamdan (Sabda: Jurnal Kajian Kebudayaan, 2024)
ABSTRACTThe object of this research is CV. Penerbit Lakeisha which was studied using 2 theories. Robert Escarpit's literary sociology theory as an umbrella theory in research and Bourdieu's cultural production arena theory as the core theory of analysis. This research is a qualitative method with data obtained through field research in the form of interviews, observation, and documentation. This research yields at least 3 results. First, the “power” arena of CV. Penerbit Lakeisha in the scope of Klaten district is one of the productive arenas in fighting over the legitimacy of works from writer agents. Second, the head of CV. Penerbit Lakeisha as the holder of power over all systems, has an accumulation of capital that will determine the decision to publish fiction books.Keywords: Arena of Cultural Production, Sociology of Literature, Distribution System, Capital, CV. Penerbit Lakeisha.